THE ADSORPTION OF IMAZAPYR BY THREE SOIL TYPES IN INDONESIA - S. TJITROSEMITO (BIOTROPIA, 1992)
The adsorption of imazapyr in three Indonesian soil types was investigated with labelled 14 C-imazapyr using Freundlich adsorption isotherm. The availability of adsorbed imazapyr to plants as affected by washing and liming was assayed using root elongation of rice seedlings. Red-Yellow Podsolic soil adsorbed imazapyr more than Andosol and sandy soil of Laladon. The adsorption was greater at lower pH. Washing seemed to reduce the concentration of imazapyr as shown by the increasing length of rice roots. On the other hand liming facilitated higher concentrations of imazapyr in the solution as shown by the reduction of rice root length. The practical implication is discussed.